Pengaruh Kompetensi Pedagogik Guru Terhadap Minat Belajar Siswa Kelas XI di SMK Katolik Santo Fransiskus Xaverius Manado - Marianus Muharli Mua; Shefry Yanny Fransisco Topit (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2025)
This study aimed to determine the level of teachers’ pedagogic competence, students’ learning interest, and the influence of teachers’ pedagogic competence on the learning interest of Grade XI students at St. Fransiskus Xaverius Catholic Vocational School, Manado. The study employed a quantitative approach with a population of 66 students and a sample of 57 students selected using the Slovin formula. Data were collected through observation, questionnaires, and documentation. Instrument validity was tested using Product Moment correlation, while reliability was measured using Cronbach’s Alpha. Data were analyzed using descriptive statistics and Product Moment correlation analysis. The findings revealed that teachers’ pedagogic competence was categorized as very good, with a coefficient value of 0.86. Students’ learning interest was also categorized as very good, with a coefficient value of 0.86. Furthermore, there was a very strong and significant influence of teachers’ pedagogic competence on students’ learning interest, indicated by an r-value of 0.940 and an effective contribution of 88% at a 5% significance level. These results indicate that teachers’ pedagogic competence plays a substantial role in enhancing students’ learning interest.